2019
DOI: 10.1038/s41419-019-1427-2
|View full text |Cite
|
Sign up to set email alerts
|

Angiomotin-p130 inhibits β-catenin stability by competing with Axin for binding to tankyrase in breast cancer

Abstract: Growing evidence indicates that Angiomotin (Amot)-p130 and Amot-p80 have different physiological functions. We hypothesized that Amot-p130 is a tumor suppressor gene in breast cancer, in contrast with the canonical oncogenicity of Amot-p80 or total Amot. To clarify the role of Amot-p130 in breast cancer, we performed real-time quantitative PCR, western blotting, flow cytometry, microarray, immunofluorescence, immunoprecipitation, and tumor sphere-formation assays in vitro, as well as tumorigenesis and limited-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…One of the hallmarks of CSCs is to sustain long telomeres through high expression of telomerase reverse transcriptase (TERT) [20]. β-catenin directly augments TERT expression through promoter binding [21].Recent studies showed that GSK3β, AXIN binding to tankyrase, and the SOX family transcription factors played key roles in the maintenance of CSC traits in breast cancers through the Wnt signaling pathway [22][23][24]. One target gene of Wnt is Leucine-rich repeat-containing G-protein-coupled receptor 5 (LGR5), a bona fide marker of adult stem cells in the gastrointestinal tract that acts to enhance Wnt/β catenin signaling [25].…”
Section: Wntsignaling and Cancer Stem Cellsmentioning
confidence: 99%
“…One of the hallmarks of CSCs is to sustain long telomeres through high expression of telomerase reverse transcriptase (TERT) [20]. β-catenin directly augments TERT expression through promoter binding [21].Recent studies showed that GSK3β, AXIN binding to tankyrase, and the SOX family transcription factors played key roles in the maintenance of CSC traits in breast cancers through the Wnt signaling pathway [22][23][24]. One target gene of Wnt is Leucine-rich repeat-containing G-protein-coupled receptor 5 (LGR5), a bona fide marker of adult stem cells in the gastrointestinal tract that acts to enhance Wnt/β catenin signaling [25].…”
Section: Wntsignaling and Cancer Stem Cellsmentioning
confidence: 99%
“…YAP interacts with β-catenin [ 24 ] and influences Wnt signaling activity positively or negatively [ 16 ]. ZO-1 promotes establishment of AJ structures by interacting with α-catenin and the actin cytoskeleton [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the classical barrier functions of TJ structures [ 20 ], downregulation of TJ proteins such as claudins, occludin, and ZO-1 reduces metastatic features, including cell migration [ 21 , 22 , 23 ]. Angiomotin (AMOT) family proteins interact with YAP and multiple components of TJs and AJs, such as β-catenin and ZO-1 [ 24 , 25 ]. The scaffolding functions of AMOT lead to sequestration of YAP to TJs, reducing nuclear YAP activity and maintaining TJ integrity and epithelial cell polarity [ 11 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in epithelial ovarian cancer, prostate cancer, liver cancer, osteosarcoma, and sinonasal tumors, AMOT was overexpressed and promoted tumor cell proliferation or invasion [10,[20][21][22][23]. AMOT participated in the regulation of several signaling pathways, including Hippo, Wnt, ERK1/2, and VEGFR-2 pathways [12,[24][25][26][27][28][29]. However, the effect of AMOT in hematopoietic malignancies has not been reported.…”
Section: Introductionmentioning
confidence: 99%